Wear-resistant refractory brick and preparation method thereof
By combining industrial solid waste such as clay sand cast dust removal ash, water glass sand recycled dust removal ash with materials such as calcium hydroxide, aluminum sol and bauxite, high-performance wear-resistant refractory bricks are prepared, which solves the problem of insufficient performance of existing refractory bricks in high temperature and high pressure environments, and achieves both cost and performance.
Patent Information
- Application Number
- CN202510125168.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-24
AI Technical Summary
Existing refractory bricks show poor high temperature and wear resistance in high temperature and high pressure environments, and it is difficult to take into account both cost and performance.
Wear-resistant refractory bricks composed of clay sand cast dust removal ash, water glass sand recycled dust removal ash, calcium hydroxide, aluminum sol and bauxite are prepared through calcination, stirring, grinding, ultrasonic treatment and other processes to form a high-density and uniform structure brick body.
It significantly improves the high temperature, wear and compressive properties of refractory bricks, with a refractory resistance of ≥1500℃, a compressive strength of ≥25Mpa, a flexural strength of ≥5Mpa, and a water absorption rate of ≤8.5%, while reducing production costs.
Abstract
Description
Technical Field
[0001] The invention relates to the field of refractory materials, and in particular to a wear-resistant refractory brick and a preparation method thereof. Background Art
[0002] As a high-temperature building material, refractory bricks play an indispensable role in industrial production. Refractory bricks are widely used in industrial production fields with high temperature environments such as steel smelting, ceramic production, cement manufacturing, glass manufacturing and heat treatment. In these fields, refractory bricks are generally used as lining materials for high-temperature equipment. For example, in the process of steel smelting, the furnaces and flues of blast furnaces, converters, electric furnaces and other equipment must be built with refractory bricks. In the process of ceramic production, refractory bricks are used as lining materials for high-temperature kilns. The quality of refractory bricks is related to the stability and safety of the production process and the life of the equipment. Therefore, the performance requirements for refractory bricks to withstand high temperature and high pressure are very high. Therefore, improving the high temperature resistance, wear resistance and pressure resistance of refractory bricks is the main research direction in the field of refractory materials. With the global consensus on environmental protection and sustainable development, the development of more environmentally friendly production processes and materials in the field of refractory materials, reducing the emission of solid waste, wastewater and waste gas, and realizing the effective utilization of resources and circular economy have also become mainstream trends.
[0003] The downstream industry of steel smelting - foundry industry will produce a large amount of solid waste. For example, in the casting process, metal is oxidized after melting to produce a large amount of metal oxides. These metal oxides form gas at high temperature, and are discharged with flue gas and condensed into solid particles when cold, forming dust ash; coal and coke that are heated to dissolve metals will also gasify at high temperature and be discharged to form dust ash; commonly used foundry sand and water glass sand will produce dust ash during the regeneration process; foundry sand will form a large amount of foundry waste sand after repeated use, etc. The reuse of these solid wastes is the core of reducing industrial costs and realizing green economy and circular economy. It can be seen that how to use solid waste to process materials with superior performance is a technical problem to be solved in the field of industry and materials.
[0004] Invention patent CN103011698A discloses a method for generating carbon bricks from associated wastes, and uses industrial solid waste to process carbon bricks, specifically using dust ash generated by ironmaking and steelmaking systems and associated resources such as iron oxide produced by steelmaking to produce carbon bricks. Although the problem of utilizing industrial solid wastes has been achieved, the process only increases the strength of the bricks by increasing the density of the bricks through vibration, and the carbon bricks produced have low high temperature resistance and wear resistance. With the development of industry, the requirements for high temperature resistance of equipment have been further improved. The development of refractory bricks with high refractoriness, high compressive strength, long service life and low cost is a problem to be faced in the field of high temperature building materials. Summary of the invention
[0005] The present invention aims at the above problems, makes up for the deficiencies of the prior art, and provides a wear-resistant refractory brick and a preparation method thereof to solve the problems arising from the above background technology.
[0006] The first aspect of the present invention provides a wear-resistant refractory brick, the raw materials of which are composed of slurry, bauxite, foundry waste sand and aluminum dihydrogen phosphate solution accounting for 1-2% of the mass percentage of the sum of the slurry, bauxite and foundry waste sand in a mass ratio of 10:6-8:3-4, wherein the mass percentage concentration of the aluminum dihydrogen phosphate solution is 12-15%; the slurry is mixed with powder and aluminum sol in a mass ratio of 10:5-6, and water is added to form a slurry with a water content of 40-50%; the powder is made of clay sand casting dust ash, water glass sand regeneration dust ash and calcium hydroxide in a mass ratio of 20-30:5-10:0.5-1.
[0007] Water glass remains in the recycled ash of water glass sand, and together with the added calcium hydroxide powder, it creates an alkaline environment for the dust removal ash of clay sand casting. Specifically, the water glass in the inorganic recycled ash is hydrolyzed to produce strong alkaline hydroxide ions, and the insoluble silicon and aluminum elements in the clay recycled ash that cannot enter the gel system are dissolved by alkaline and converted into ionic forms. The silicon and aluminum in ionic form react with silicate and hydroxide to form small particle gels, which aggregate to form a gel skeleton and finally form a stable gel structure. This stimulates the activity of the inactivated clay sand casting dust removal ash after high temperature treatment, increases its viscosity, and is conducive to the subsequent extrusion molding of brick blanks. At the same time, water glass can also neutralize the acidity of the sol, mix with aluminum sol to form a composite gel of aluminate and silicate, enhance the strength of the brick in the wet blank state, and the brick blanks can be stacked denser and higher, thereby improving the efficiency of mechanical operation and reducing energy consumption.
[0008] Preferably, the mass ratio of the clay sand casting dust ash, the water glass sand regeneration dust ash and the calcium hydroxide is 20-30:5-7:0.5-1.
[0009] Preferably, the mass ratio of the powder to the aluminum sol is 10:6.
[0010] Preferably, the mass ratio of the slurry, the bauxite and the foundry waste sand is 10:6-7:3.5-4.
[0011] Preferably, the frequency of the ultrasonic treatment is 28-32 kHz, and the time is 1-2 min.
[0012] Preferably, the solid content of the aluminum sol is 10-12%.
[0013] The second aspect of the present invention also provides a method for preparing a wear-resistant refractory brick, the method comprising the following steps:
[0014] 1) Preparation of powder: calcining the clay sand casting dust ash, cooling it to room temperature, mixing the clay sand casting dust ash with water glass sand regeneration dust ash and calcium hydroxide powder in a mass ratio of 20-30:5-10:0.5-1, stirring, grinding, sieving, and preparing powder;
[0015] 2) Slurry preparation: the powder prepared in step (1) is mixed with aluminum sol and water, and stirred to prepare a slurry with a water content of 40-50%;
[0016] 3) Wet material preparation: the slurry prepared in step (2) is mixed with bauxite and foundry waste sand in a mass ratio of 10:6-8:3-4, and a 12-15% by mass aluminum dihydrogen phosphate solution is sprayed into the mixture, wherein the amount of the aluminum dihydrogen phosphate solution is 1-2% of the total mass of the slurry, bauxite and foundry waste sand to prepare a wet material;
[0017] 4) blank making: the wet material prepared in step (3) is made into a brick blank;
[0018] 5) Drying: drying the bricks obtained in step (4) at a constant temperature, and then drying them with hot air;
[0019] 6) Firing: Firing the bricks dried in step (5) to obtain finished bricks.
[0020] Preferably, the slurry prepared in step 2) is subjected to an ultrasonic treatment step, the frequency of the ultrasonic treatment being 28-32 kHz and the time being 1-2 min. The ultrasonic treatment evenly disperses the aluminum sol in the slurry system and wraps the raw materials with lower refractoriness in the raw materials so that they will not be softened and their structure will not be destroyed when encountering high temperature.
[0021] Preferably, the calcination temperature in the step 1) is 600-700°C, and the calcination is stopped when the clay sand casting dust ash completely changes from black to yellow. Clay sand casting dust ash is mixed with organic dust generated during the combustion of fuel. By calcining, the organic matter in the clay sand casting dust ash is removed, which can improve the strength, stability and safety of the brick during the production process. If the calcination temperature is too low, the organic matter will not be completely decomposed. In the subsequent brick firing process, the organic matter will decompose at high temperature to produce gas, forming pores in the brick body, thereby reducing the density and strength of the brick. If the calcination temperature is too high, the activity of the clay sand casting dust ash will be further destroyed, the viscosity will be reduced, and the brick blank will be difficult to form. The calcination temperature is between 600-700°C, which can not only completely remove the organic residues, but also retain a certain activity of the clay sand casting dust ash. Specifically, the calcination temperature is 600° C., 620° C., 640° C., 650° C., 670° C., 690° C., 700° C. or an interval value thereof.
[0022] Preferably, the stirring speed is 1000-1500 rpm.
[0023] Preferably, the grinding is performed using a ball mill, and the particle size of the powder is ≤74 μm.
[0024] Preferably, in step 4), vacuum extrusion molding is adopted, the extrusion pressure is 3 to 4 MPa, and the vacuum degree is -0.096 to -0.08 MPa.
[0025] Preferably, the constant temperature drying temperature in step 5) is 20-25°C, and the drying time is 24-36h; the hot air drying temperature is 60-80°C, and the drying is stopped when the moisture content of the brick is ≤2.5%.
[0026] Preferably, the firing in step 6) is preheating at 200-300°C for 3-4h, heating to 950-1150°C at an average rate of 1.5°C / min and keeping warm for 1-2h, heating to 1350-1450°C at an average rate of 1.5°C / min and keeping warm for 2-3h, cooling to room temperature to obtain finished bricks.
[0027] Compared with the bricks in the prior art, the present invention has the following beneficial effects:
[0028] (1) Compared with the raw materials for preparing wear-resistant refractory bricks in the conventional method, the raw materials of the present invention adopt industrial solid wastes such as clay sand casting dust ash and water glass sand regeneration dust ash, which is not only environmentally friendly but also greatly reduces the production cost of bricks.
[0029] (2) The water glass component and calcium hydroxide in the water glass sand regeneration dust ash in the wear-resistant refractory brick raw material of the present invention can stimulate the viscosity of the high-temperature inactivated sand casting dust ash, making the bricks easy to extrude and form. The brick pressing equipment does not need high pressure output, the energy consumption is reduced, and the production cost is further reduced.
[0030] (3) High strength of wet bricks: The aluminum sol added to the raw materials can generate a composite gel of aluminate and silicate in the alkaline environment created by water glass and calcium hydroxide, which makes the particles of casting dust more tightly bonded, the wet bricks more dense, and the strength increases. The bricks can be stacked denser and higher, and the efficiency of transferring wet bricks is higher, which reduces the energy consumption of brick production.
[0031] (4) The present invention adds an ultrasonic treatment step to the brick preparation process. Ultrasonic waves reduce particle agglomeration and promote more uniform wrapping of the composite sol on the surface of dust particles, thereby improving the uniformity, density and fire resistance of the bricks, and further significantly improving the flexural strength and compressive strength of the bricks.
[0032] (5) The addition of bauxite to the raw materials greatly improves the wear resistance and fire resistance of the bricks. During the high-temperature firing process of the bricks, the diaspore and kaolinite in the bauxite undergo different chemical reactions and phase changes in different temperature ranges, and finally form a network interwoven structure of mullite phase and glass phase inside the brick body, which enhances the bonding strength, high temperature resistance and wear resistance of the material.
[0033] (6) The wear-resistant refractory bricks prepared by the preparation method of the present invention have a refractoriness of ≥1500°C, a compressive strength of ≥25Mpa, a flexural strength of ≥5Mpa, and a water absorption rate of ≤8.5%. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0035] The embodiment of the present invention solves the problem that the refractory bricks in the prior art have poor high temperature resistance and wear resistance and cannot take into account the cost by providing a wear-resistant refractory brick and a preparation method thereof.
[0036] The parts in the present invention refer to parts by mass.
[0037] Example 1
[0038] A wear-resistant refractory brick is prepared by the following method:
[0039] (1) Preparation of powder: calcining clay sand casting dust at 600° C. until the clay sand casting dust changes from black to yellow, cooling to room temperature, taking 200 parts by mass of the calcined and cooled clay sand casting dust, 50 parts by mass of water glass sand regeneration dust, and 5 parts by mass of calcium hydroxide powder, and mixing them uniformly with a high-speed stirrer at 1000 rpm, grinding the mixture in a ball mill, and passing through a 200 mesh sieve to prepare a powder with a particle size of ≤74 μm.
[0040] (2) Preparation of slurry: 100 parts of the powder prepared in step (1) were mixed with 50 parts of aluminum sol having a solid content of 10%, and an appropriate amount of water was added to prepare a slurry having a water content of 40%. The slurry was subjected to ultrasonic treatment at a frequency of 28 kHz for 1 min.
[0041] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment are mixed evenly with 60 parts of bauxite and 30 parts of foundry waste sand; 1.9 parts of aluminum dihydrogen phosphate are taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 15%; and all of the above-mentioned dihydrogen phosphate solution is sprayed into the mixture to prepare a wet material.
[0042] (4) Brick making: The wet material in step (3) is made into bricks using a brick making machine, and the brick making machine is set to have an extrusion pressure of 4 MPa and a vacuum degree of -0.095 MPa.
[0043] (5) Drying: Place the finished bricks in a drying room and dry at 20°C for 36 hours, then introduce hot air at 60°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0044] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 200°C for 4 h, then heated to 950°C at an average rate of 1.5°C / min and kept for 2 h. Then, they are heated to 1350°C at an average rate of 1.5°C / min and kept for 3 h. After firing, they are cooled to obtain finished bricks.
[0045] Example 2
[0046] A wear-resistant refractory brick is prepared by the following method:
[0047] (1) Preparation of powder: calcining clay sand casting dust removal ash at 700° C. until the clay sand casting dust removal ash completely changes from black to yellow, and then cooling to room temperature. Taking 300 parts by mass of the calcined and cooled clay sand casting dust removal ash, 100 parts by mass of water glass sand regeneration dust removal ash, and 10 parts by mass of calcium hydroxide powder, and mixing them evenly with a high-speed stirrer at 1500 rpm. Grinding the mixture in a ball mill, passing through a 200-mesh sieve, and preparing a powder with a particle size of ≤74 μm.
[0048] (2) Preparation of slurry: 100 parts of the powder prepared in step (1) were mixed with 60 parts of aluminum sol having a solid content of 12%, and an appropriate amount of water was added to prepare a slurry having a water content of 50%. The slurry was subjected to ultrasonic treatment at a frequency of 32 kHz for 2 min.
[0049] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment were taken and mixed evenly with 80 parts of bauxite and 40 parts of foundry waste sand; 4.4 parts of aluminum dihydrogen phosphate were taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 12%; and all of the above-mentioned dihydrogen phosphate solution was sprayed into the mixture to prepare a wet material.
[0050] (4) Blank making: The wet material in step (3) is made into brick blanks using a brick making machine, and the brick making machine is set to an extrusion pressure of 3 MPa and a vacuum degree of -0.08 MPa.
[0051] (5) Drying: Place the finished bricks in a drying room and dry at 25°C for 28 hours, then introduce hot air at 70°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0052] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 200°C for 3 h, then heated to 1150°C at an average rate of 1.5°C / min and kept for 1 h. Then, they are heated to 1450°C at an average rate of 1.5°C / min and kept for 2 h. After firing, they are gradually cooled to obtain finished bricks.
[0053] Example 3
[0054] A wear-resistant refractory brick is prepared by the following method:
[0055] (1) Preparation of powder: calcining clay sand casting dust removal ash at 650° C. until the clay sand casting dust removal ash completely changes from black to yellow, cooling to room temperature, taking 250 parts by mass of the calcined and cooled clay sand casting dust removal ash, 75 parts by mass of water glass sand regeneration dust removal ash, and 8 parts by mass of calcium hydroxide powder, and mixing them uniformly with a high-speed stirrer at 1250 rpm, grinding the mixture in a ball mill, and passing through a 200 mesh sieve to prepare a powder with a particle size of ≤74 μm.
[0056] (2) Preparation of slurry: 100 parts of the powder prepared in step (1) were mixed with 55 parts of aluminum sol having a solid content of 12%, and an appropriate amount of water was added to prepare a slurry having a water content of 45%. The slurry was subjected to ultrasonic treatment at a frequency of 30 kHz for 1 min.
[0057] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment were taken and mixed evenly with 70 parts of bauxite and 35 parts of foundry waste sand; 3 parts of aluminum dihydrogen phosphate were taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 13.5%; and all of the above-mentioned dihydrogen phosphate solution was sprayed into the mixture to prepare a wet material.
[0058] (4) Brick making: The wet material in step (3) is made into bricks using a brick making machine. The brick making machine is set to have an extrusion pressure of 3.5 MPa and a vacuum degree of -0.09 MPa.
[0059] (5) Drying: Place the finished bricks in a drying room and dry them at 23°C for 24 hours, then introduce hot air at 60°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0060] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 250°C for 3.5 hours, then heated to 1050°C at an average rate of 1.5°C / min and kept for 1.5 hours. Then, they are heated to 1400°C at an average rate of 1.5°C / min and kept for 2.5 hours. After firing, they are gradually cooled to obtain finished bricks.
[0061] Example 4
[0062] The difference between Example 4 and Example 3 is that ultrasonic treatment is not performed in step (2); the other steps are the same.
[0063] Comparative Example 1
[0064] A wear-resistant refractory brick is prepared by the following method:
[0065] (1) Powder preparation: calcining the clay sand casting dust removal ash at 650° C. until the clay sand casting dust removal ash completely changes from black to yellow, cooling to room temperature, grinding the calcined clay sand casting dust removal ash in a ball mill, and passing through a 200-mesh sieve to prepare a powder with a particle size of ≤74 μm.
[0066] (2) Preparation of slurry: 100 parts by mass of the powder prepared in step (1) were mixed with 55 parts of aluminum sol having a solid content of 12%, and an appropriate amount of water was added to prepare a slurry having a water content of 45%. The slurry was subjected to ultrasonic treatment at a frequency of 30 kHz for 1 min.
[0067] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment were taken and mixed evenly with 70 parts of bauxite and 35 parts of foundry waste sand; 3 parts of aluminum dihydrogen phosphate were taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 13.5%; and all of the above-mentioned dihydrogen phosphate solution was sprayed into the mixture to prepare a wet material.
[0068] (4) Brick making: The wet material in step (3) is made into bricks using a brick making machine. The brick making machine is set to have an extrusion pressure of 3.5 MPa and a vacuum degree of -0.09 MPa.
[0069] (5) Drying: Place the finished bricks in a drying room and dry them at 23°C for 24 hours, then introduce hot air at 60°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0070] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 250°C for 3.5 hours, then heated to 1050°C at an average rate of 1.5°C / min and kept for 1.5 hours. Then, they are heated to 1450°C at an average rate of 1.5°C / min and kept for 2 hours. After firing, they are gradually cooled to obtain finished bricks.
[0071] Comparative Example 2
[0072] A wear-resistant refractory brick is prepared by the following method:
[0073] (1) Preparation of powder: calcining clay sand casting dust removal ash at 650° C. until the clay sand casting dust removal ash completely changes from black to yellow, cooling to room temperature, taking 250 parts by mass of the calcined and cooled clay sand casting dust removal ash, 75 parts by mass of water glass sand regeneration dust removal ash, and 8 parts by mass of calcium hydroxide powder, and mixing them uniformly with a high-speed stirrer at 1250 rpm, grinding the mixture in a ball mill, and passing through a 200 mesh sieve to prepare a powder with a particle size of ≤74 μm.
[0074] (2) Preparation of slurry: Take 100 parts of the powder prepared in step (1), add appropriate amount of water to prepare a slurry with a water content of 45%, and subject the slurry to ultrasonic treatment at a frequency of 30 kHz for 1 min.
[0075] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment were taken and mixed evenly with 70 parts of bauxite and 35 parts of foundry waste sand; 3 parts of aluminum dihydrogen phosphate were taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 13.5%; and all of the above-mentioned dihydrogen phosphate solution was sprayed into the mixture to prepare a wet material.
[0076] (4) Brick making: The wet material in step (3) is made into bricks using a brick making machine. The brick making machine is set to have an extrusion pressure of 3.5 MPa and a vacuum degree of -0.09 MPa.
[0077] (5) Drying: Place the finished bricks in a drying room and dry them at 23°C for 24 hours, then introduce hot air at 60°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0078] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 250°C for 3.5 hours, then heated to 1050°C at an average rate of 1.5°C / min and kept for 1.5 hours. Then, they are heated to 1400°C at an average rate of 1.5°C / min and kept for 2.5 hours. After firing, they are gradually cooled to obtain finished bricks.
[0079] Comparative Example 3
[0080] A wear-resistant refractory brick is prepared by the following method:
[0081] (1) Preparation of powder: calcining clay sand casting dust removal ash at 650° C. until the clay sand casting dust removal ash completely changes from black to yellow, cooling to room temperature, taking 250 parts by mass of the calcined and cooled clay sand casting dust removal ash, 75 parts by mass of water glass sand regeneration dust removal ash, and 8 parts by mass of calcium hydroxide powder, and mixing them uniformly with a high-speed stirrer at 1250 rpm, grinding the mixture in a ball mill, and passing through a 200 mesh sieve to prepare a powder with a particle size of ≤74 μm.
[0082] (2) Preparation of slurry: 100 parts of the powder prepared in step (1) were mixed with 55 parts of aluminum sol having a solid content of 12%, and an appropriate amount of water was added to prepare a slurry having a water content of 45%. The slurry was subjected to ultrasonic treatment at a frequency of 30 kHz for 1 min.
[0083] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment are taken and mixed evenly with 35 parts of foundry waste sand; 3 parts of aluminum dihydrogen phosphate are taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 13.5%; and all of the above-mentioned dihydrogen phosphate solution is sprayed into the mixture to prepare a wet material.
[0084] (4) Brick making: The wet material in step (3) is made into bricks using a brick making machine. The brick making machine is set to an extrusion pressure of 3.5 MPa and a vacuum degree of -0.09 MPa.
[0085] (5) Drying: Place the finished bricks in a drying room and dry them at 23°C for 24 hours, then introduce hot air at 60°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0086] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 250°C for 3.5 hours, then heated to 1050°C at an average rate of 1.5°C / min and kept for 1.5 hours. Then, they are heated to 1400°C at an average rate of 1.5°C / min and kept for 2.5 hours. After firing, they are gradually cooled to obtain finished bricks.
[0087] Comparative Example 4
[0088] A wear-resistant refractory brick is prepared by the following method:
[0089] (1) Preparation of powder: calcining clay sand casting dust at 650° C. until the clay sand casting dust changes from black to yellow, cooling to room temperature, taking 250 parts by weight of the calcined and cooled clay sand casting dust, 45 parts by weight of water glass sand regeneration dust, and 8 parts by weight of calcium hydroxide powder, and mixing them uniformly with a high-speed stirrer at 1250 rpm, grinding the mixture in a ball mill, and passing through a 200 mesh sieve to prepare a powder with a particle size of ≤74 μm.
[0090] (2) Preparation of slurry: 100 parts of the powder prepared in step (1) were mixed with 55 parts of aluminum sol having a solid content of 12%, and an appropriate amount of water was added to prepare a slurry having a water content of 45%. The slurry was subjected to ultrasonic treatment at a frequency of 30 kHz for 1 min.
[0091] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment were taken and mixed evenly with 70 parts of bauxite and 35 parts of foundry waste sand; 3 parts of aluminum dihydrogen phosphate were taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 13.5%; and all of the above-mentioned dihydrogen phosphate solution was sprayed into the mixture to prepare a wet material.
[0092] (4) Brick making: The wet material in step (3) is made into bricks using a brick making machine. The brick making machine is set to have an extrusion pressure of 3.5 MPa and a vacuum degree of -0.09 MPa.
[0093] (5) Drying: Place the finished bricks in a drying room and dry them at 23°C for 24 hours, then introduce hot air at 60°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0094] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 250°C for 3.5 hours, then heated to 1050°C at an average rate of 1.5°C / min and kept for 1.5 hours. Then, they are heated to 1400°C at an average rate of 1.5°C / min and kept for 2.5 hours. After firing, they are gradually cooled to obtain finished bricks.
[0095] Comparative Example 5
[0096] A wear-resistant refractory brick is prepared by the following method:
[0097] (1) Preparation of powder: calcining clay sand casting dust removal ash at 650° C. until the clay sand casting dust removal ash completely changes from black to yellow, cooling to room temperature, taking 250 parts by mass of the calcined and cooled clay sand casting dust removal ash, 75 parts by mass of water glass sand regeneration dust removal ash, and 8 parts by mass of calcium hydroxide powder, and mixing them uniformly with a high-speed stirrer at 1250 rpm, grinding the mixture in a ball mill, and passing through a 200 mesh sieve to prepare a powder with a particle size of ≤74 μm.
[0098] (2) Preparation of slurry: 100 parts of the powder prepared in step (1) were mixed with 55 parts of aluminum sol having a solid content of 12%, and an appropriate amount of water was added to prepare a slurry having a water content of 45%. The slurry was subjected to ultrasonic treatment at a frequency of 30 kHz for 1 min.
[0099] (3) Preparation of wet material: 100 parts of the slurry after ultrasonic treatment were taken and mixed evenly with 55 parts of bauxite and 35 parts of foundry waste sand; 3 parts of aluminum dihydrogen phosphate were taken to prepare an aluminum dihydrogen phosphate solution with a mass percentage concentration of 13.5%; and all of the above-mentioned dihydrogen phosphate solution was sprayed into the mixture to prepare a wet material.
[0100] (4) Brick making: The wet material in step (3) is made into bricks using a brick making machine. The brick making machine is set to an extrusion pressure of 3.5 MPa and a vacuum degree of -0.09 MPa.
[0101] (5) Drying: Place the finished bricks in a drying room and dry them at 23°C for 24 hours, then introduce hot air at 60°C until the moisture content in the bricks is ≤2.5%. The moisture content here is measured by a conventional electronic moisture meter.
[0102] (6) Firing: The dried bricks are stacked and sent into the tunnel kiln by a pushing device. They are kept in a preheated zone at 250°C for 3.5 hours, then heated to 1050°C at an average rate of 1.5°C / min and kept for 1.5 hours. Then, they are heated to 1450°C at an average rate of 1.5°C / min and kept for 2 hours. After firing, they are gradually cooled to obtain finished bricks.
[0103] Comparative Example 6
[0104] Wear-resistant refractory bricks purchased in the building materials market.
[0105] The refractoriness, compressive strength, flexural strength and water absorption of Examples 1-4 and Comparative Examples 1-6 were tested. The compressive strength test was performed using a fully automatic pressure testing machine in the prior art. The flexural strength test was performed using a three-point bending method in the prior art. The water absorption test was performed using a weight method in the prior art.
[0106] The main performance test results of the wear-resistant refractory bricks prepared in the above examples and comparative examples are shown in the following table:
[0107] Table 1
[0108] Example Refractoriness(℃) Compressive strength(Mpa) Flexural strength(Mpa) Water absorption (%) Example 1 1550 28.8 5.8 8.3 Example 2 1600 28.5 5.9 8.5 Example 3 1600 30.6 6.6 7.4 Example 4 1580 29.3 6.1 7.9 Comparative Example 1 1550 26.2 5.3 9.1 Comparative Example 2 1400 28.3 5.7 8.8 Comparative Example 3 1300 26.2 5.1 9.6 Comparative Example 4 1480 27.8 5.9 8.9 Comparative Example 5 1350 27.5 5.9 8.6 Comparative Example 6 1450 25.6 5.3 9.2
[0109] It can be seen from the test results of Examples 1-4 and Comparative Examples 1-6 that the wear-resistant refractory bricks prepared by the present invention have a refractoriness of ≥1500℃, a compressive strength of ≥25Mpa, a flexural strength of ≥5MPa, and a water absorption rate of ≤8.5%, which is significantly better than the performance of the refractory bricks prepared in the comparative example. It can be seen from the comparison between Example 3 and Example 4 that the addition of an ultrasonic treatment step in the process of preparing wear-resistant refractory bricks can improve the compressive strength, flexural strength and refractoriness of the brick body. The improvement of compressive and flexural strengths will increase the wear resistance of the brick body. This is because the ultrasonic wave can reduce the agglomeration of dust particles and promote the composite sol of aluminum sol and silicate to be more evenly wrapped on the surface of dust particles, making the brick structure more uniform and dense. It can be seen from the comparison between Example 3 and Comparative Example 1 that for bricks prepared by using clay sand casting dust removal ash, water glass and alkaline environment are the key components for brick body forming and improving brick body strength. Combined with Comparative Example 4, it can be seen that when the water glass component is not added or the amount added is not within the scope of the present invention, the compressive and flexural strength of the brick is greatly reduced. The reason is that the alkalinity provided by water glass and calcium hydroxide is too small, and the activation ability of clay sand casting dust ash is insufficient. At the same time, aluminate and silicate cannot form a composite gel, so the bonding degree between the dust ash particles is insufficient, resulting in a decrease in the compressive and flexural strength of the brick body. The appropriate proportion of water glass components set by the present invention can overcome the above problems. By comparing Example 3 and Comparative Example 2, it can be seen that adding aluminum sol to the components of the brick significantly improves the flexural strength of the brick body. In the alkaline environment provided by water glass, the aluminum sol forms a composite gel with silicate, which further improves the density of the brick. By comparing Example 3 with Comparative Examples 3 and 5, it can be seen that bauxite is a component that improves the refractory properties of the brick body. Within the appropriate addition range of the present invention, bauxite can greatly improve the refractory properties. It can be seen that the refractory and wear-resistant bricks of the present invention have high uniformity and density, high compressive strength, flexural strength and wear-resistant and fire-resistant properties, and due to the dense structure, the water absorption capacity is reduced. It can be seen that the wear-resistant and refractory bricks prepared by the present invention have excellent performance.
[0110] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A wear-resistant refractory brick, characterized in that: The raw materials are composed of slurry, bauxite, foundry waste sand and aluminum dihydrogen phosphate solution with a mass ratio of 10:6-8:3-4, accounting for 1-2% of the mass percentage of the sum of the slurry, bauxite and foundry waste sand, wherein the mass percentage concentration of the aluminum dihydrogen phosphate solution is 12-15%; the slurry is mixed with powder and aluminum sol with a mass ratio of 10:5-6, and water is added to form a slurry with a water content of 40-50%; the powder is made of clay sand casting dust removal ash, water glass sand regeneration dust removal ash and calcium hydroxide with a mass ratio of 20-30:5-10:0.5-1.
2. A wear-resistant refractory brick according to claim 1, characterized in that: The mass ratio of the clay sand casting dust ash, the water glass sand regeneration dust ash and the calcium hydroxide is 20-30:5-7.5:0.5-1; and / or, the mass ratio of the powder and the aluminum sol is 10:6; and / or, the mass ratio of the slurry, the bauxite and the casting waste sand is 10:6-7:3.5-4.
3. A wear-resistant refractory brick according to claim 1, characterized in that: The slurry is subjected to ultrasonic treatment, the frequency of the ultrasonic treatment is 28-32 kHz, and the time is 1-2 min.
4. A wear-resistant refractory brick according to claim 1, characterized in that: The solid content of the aluminum sol is 10-12%.
5. A method for preparing a wear-resistant refractory brick according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Preparation of powder: calcining the clay sand casting dust ash, cooling it to room temperature, mixing the clay sand casting dust ash with the water glass sand regeneration dust ash and the calcium hydroxide powder in a mass ratio of 20-30:5-10:0.5-1, stirring, grinding, sieving, and preparing powder; 2) Slurry preparation: mixing the powder prepared in step (1) with the aluminum sol and water, stirring to prepare a slurry with a water content of 40-50%; 3) Wet material preparation: the slurry prepared in step (2) is mixed with the bauxite and the foundry waste sand in a mass ratio of 10:6-8:3-4, and a 12-15% by mass aluminum dihydrogen phosphate solution is sprayed into the mixture, wherein the amount of the aluminum dihydrogen phosphate solution is 1-2% of the total mass of the slurry, the bauxite and the foundry waste sand, to prepare a wet material; 4) blank making: the wet material prepared in step (3) is made into a brick blank; 5) Drying: drying the bricks obtained in step (4) at a constant temperature, and then drying them with hot air; 6) Firing: Firing the bricks dried in step (5) to obtain finished bricks.
6. The method for preparing a wear-resistant refractory brick according to claim 5, characterized in that: The method further comprises subjecting the slurry prepared in step 2) to ultrasonic treatment, wherein the frequency of the ultrasonic treatment is 28-32 kHz and the time is 1-2 minutes.
7. The method for preparing a wear-resistant refractory brick according to claim 5, characterized in that: The calcination temperature in step 1) is 600-700° C., the stirring speed is 1000-1500 rpm, and the particle size of the powder is ≤74 μm.
8. The method for preparing a wear-resistant refractory brick according to claim 5, characterized in that: In the step 4), the bricks are formed by vacuum extrusion, the extrusion pressure is 3 to 4 MPa, and the vacuum degree is -0.096 to -0.08 MPa.
9. The method for preparing a wear-resistant refractory brick according to claim 5, characterized in that: The constant temperature drying temperature in step 5) is 20-25°C, and the drying time is 24-36h; the hot air drying temperature is 60-80°C, and the drying is stopped when the moisture content of the brick is ≤2.5%.
10. The method for preparing a wear-resistant refractory brick according to claim 5, characterized in that: The firing process of step 6) is specifically preheating at 200-300°C for 3-4h, heating to 950-1150°C and keeping warm for 1-2h, heating to 1350-1450°C and keeping warm for 2-3h, cooling to room temperature, and obtaining finished bricks.